Punicalagin Alleviates Psoriasis by Inhibiting NF-κB-Mediated IL-1β Transcription and Caspase-1-Regulated IL-1β Secretion - Tang, Lipeng; Li, Tong; Zhang, Bowen; Zhang, Zihao; Sun, Xiaoyi; Zhu, Ying; Feng, Bing; Su, Zuqing; Yang, Laijun; Li, Hongxia; Liu, Huazhen; Chen, Yuchao; et al. (Frontiers in Pharmacology, 2022)
Psoriasis is a chronic and inflammatory skin disorder characterized by inflammation and epidermal hyperplasia. Punicalagin (PUN) is a main active ingredient of pomegranate peel with multiple biological activities, such as antibacterial, antioxidant and anti-tumor effects. However, the potential effect of PUN on psoriasis remains unknown. Here we found that PUN effectively alleviates the severity of psoriasis-like symptoms in imiquimod (IMQ)-induced psoriatic mouse model. Mechanistically, PUN potently suppresses the aberrant upregulation of IL-1β and subsequent IL-1β-mediated inflammatory cascade in keratinocytes by inhibiting NF-κB activation and cleaved caspase-1 expression in vitro and in vivo. Taken together, our findings indicate that PUN can relieve psoriasis by repressing NF-κB-mediated IL-1β transcription and caspase-1-regulated IL-1β secretion, which provide evidence that PUN might represent a novel and promising candidate for the treatment of psoriasis.